Motivational Hierarchy in the Chinese Brain: Primacy of the Individual Self, Relational Self, or Collective Self? - Zhu, Xiangru; Wu, Haiyan; Yang, Suyong; Gu, Ruolei (Frontiers in Psychology, 2016)
According to the three-tier hierarchy of motivational potency in the self system, the self can be divided into individual self, relational self, and collective self, and individual self is at the top of the motivational hierarchy in Western culture. However, the motivational primacy of the individual self is challenged in Chinese culture, which raises the question about whether the three-tier hierarchy of motivational potency in the self system can be differentiated in the collectivist brain. The present study recorder the event-related potentials (ERPs) to evaluate brain responses when participants gambled for individual self, for a close friend (relational self), or for the class (collective self). The ERP results showed that when outcome feedback was positive, gambling for individual self evoked a larger reward positivity compared with gambling for a friend or for the class, while there is no difference between the latter two conditions. In contrast, when outcome feedback was negative, no significant effect was found between conditions. The present findings provide direct electrophysiological evidence that individual self is at the top of the three-tier hierarchy of the motivational system in the collectivist brain, which supports the classical pancultural view that individual self has motivational primacy.